Icelandic managers in fishing companies : to what extent do Icelandic mnagers and middle mangers in Iceland's twenty largest fishing companies fit into predetermined cultural dimensions? - Hjörtur Smári Vestfjörð 1988- (2011)
In this research paper the focus is on culture and leadership amongst Icelandic managers in fishing companies. The main goal of the research was to compare the Icelandic leader in general with Icelandic leaders in fishing companies and find out if there was any difference between them in cultural orientation or leadership style. The researcher thought it might be useful and informative to investigate if cultural orientation and leadership styles vary amongst professions. Quantitative research methodology was applied in this study. The researcher used primary sources whenever possible. He formed a questionnaire and then analyzed the results. Ninety-seven questionnaires were sent to managers and middle managers in twenty largest fishing companies in Iceland. Thirty-four responses were received with a response rate of 35.1%. Whenever the researcher did not find primary sources, comprehensive databases were used, such as the web of science and others. The researcher also used previous studies on culture from various authors to make this report. The results of the analysis concluded that Icelandic managers in general and managers specifically in fishing companies have very similar cultural orientations and leadership styles. The questionnaire revealed that there is a high correlation between the managers’ leadership styles, whereas majority of respondents preferred using delegating management method. The correlation was also visible when examining the cultural dimensions, the questionnaire revealed that the managers were very egalitarian, collective and had a low power distance, like the Icelandic manager in general. The main difference between the managers was that leaders in fishing companies are highly uncertainty avoidant, while Icelandic managers in general are not. This research indicates that managers in fishing companies do not differentiate their cultural orientation or leadership style from Icelandic managers in general. Therefore it can be concluded, that in this case, the managers’ profession does not ...